Early-life antibiotic exposure and type 1 diabetes risk: a systematic review and meta-analysis - De Pasquale, Callum; Harrison, Leonard C. (Frontiers in Endocrinology, 2026)
ObjectiveAntibiotic exposure impacts the gut microbiome and potentially, in an infant, the developing immune system, with implications for the emergence of immune disorders such as type 1 diabetes (T1D). Reports of early-life antibiotic exposure on risk for T1D are inconsistent. We aimed to perform a systematic review and meta-analysis of the association between antibiotic exposure in early life and the development of T1D.MethodsObservational studies were assembled that reported an association between early-life antibiotic exposure and the development of T1D. Four early-life periods were covered: 12 months preconception, prenatal (in pregnancy), neonatal and up to 24 months postnatal. Medline, Embase, Web of Science Core Collection, and Scopus were searched from inception to August 28, 2024. All records were imported into Covidence for automated deduplication, abstract screening and full-text screening by two independent reviewers. Data from 20 studies and 10, 960 T1D cases were extracted and analysed using a random effects meta-analysis. Pooled odds ratios (ORs) and hazard ratios (HRs) with associated 95% confidence intervals (CIs) were calculated.ResultsIn the preconception period, maternal exposure to macrolide (OR = 1.23 [95% CI: 1.02–1.48]), sulfonamide/trimethoprim (OR = 1.34 [95% CI: 1.07–1.69]) or tetracycline (OR = 1.26 [95% CI: 1.11–1.44]) antibiotics was associated with an increased odds of T1D. Prenatal, neonatal and postnatal antibiotic exposure was not significantly associated with T1D.ConclusionPreconception exposure to specific antibiotic classes may represent a modifiable maternal risk factor for T1D in the offspring. This would have implications for antibiotic prescribing guidelines but requires validation by the further study of defined antibiotic classes and their exact timing of preconception exposure.Systematic review registrationThe protocol was pre-registered on PROSPERO (CRD42024589374) and followed PRISMA guidelines.